A fűszerpaprika, mint hagyományos magyar termékünk fogyasztási szokásainak elemzése - Panyor, Ágota (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The certain countries of the European Union can preserve their competitiveness only in that manner if the member states can keep their individuality and identity on a long distance. For the sake of the cause, it is important to provide most of our unique, traditional hungarian products with communal trademark to protect our values and to reserve the traditional technologies. The produce of Red Paprika of the landscape district of Szeged and Kalocsa is under communal trademark proccess and hopefully it will get it in this year.